The influence of increasing dietary methionine on the performance of the early-weaned pig (10 ± 4 d of age) - K Q Owen; L J Kats; B T Richert; Jim L Nelssen; Robert D Goodband; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1994)
Four hundred thirty-five pigs (initially 7.7 lb and 10.1 ± 4 d of age) were used to determine the influence of increasing dietary methionine on growth performance of the early-weaned pig (10 d of age). Pigs were blocked by weight in a randomized complete block design, resulting in six to 13 pigs per pen and a total of eight pens per treatment. Experimental diets were fed from d 0 to 21 postweaning. Dietary methionine levels were achieved by adding increasing liquid methionine (Alimet) to a common basal diet. The control diet was corn-based and contained 8.7% moist extruded soy protein concentrate, 10% spray-dried porcine plasma, 25% dried whey, 5% dried skim milk, 3% fish meal, and 1.75% spray-dried blood meal. All diets were formulated to contain 1.8% lysine. Liquid methionine replaced sucrose in the control diet to provide dietary methionine levels of .36, .40, .44, .48, .52, and .56%. Each diet contained .62% cystine and 704 g of added choline chloride (60%). During d o to 7 postweaning, average daily gain (ADG) and feed efficiency (F/G) were improved by increasing dietary methionine, with optimal performance observed between .48 and .52% dietary methionine. However, average daily feed intake (ADFI) was not affected by dietary methionine. For the entire period (d 0 to 21 postweaning), ADG and F/G were improved with increasing dietary methionine and optimized between .48 to .52% dietary methionine. On d 7 postweaning, plasma urea nitrogen was reduced as dietary methionine increased, with pigs fed the .52% methionine having the lowest plasma urea nitrogen concentrations. These data suggest that the early-weaned pig (1O-d of age) needs approximately .48 to .52% dietary methionine when fed a diet containing 1.8% lysine to optimize growth performance.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Methionine; Starter pigs; Growth